Nutrition knowledge of adolescents in a family setting in Geelong, Australia - Tienboon P. (2014)
A family study of nutrition knowledge was carried out in 213 families in the city of Geelong, Victoria, Australia. On average, mothers had the highest number of correct answers [mean 8.0 (S.D. 1.4)] followed by fathers [mean 7.8 (S.D. 1.5)], adolescent girls [mean 6.4 (S.D. 1.8)] and adolescent boys [mean 6.2 (S.D. 1.5)]. A highly significant difference, in the score obtained, was found between parents and adolescents (p < 0.001). On average, the percentage of 'do not know' answers was twice as high among adolescents (26%) as among parents (11%). Negative correlations which ranged from -0.10 for girls to -0.23 for fathers were found between the knowledge score obtained by the subjects and socioeconomic status. Parents' knowledge score was independent of their educational level (p > 0.05). Mothers with TAFE (Technical And Further Education) qualifications obtained the highest score (8.7).